1999
DOI: 10.1046/j.1365-2486.1999.00234.x
|View full text |Cite
|
Sign up to set email alerts
|

The photosynthesis – leaf nitrogen relationship at ambient and elevated atmospheric carbon dioxide: a meta‐analysis

Abstract: Esthation of leaf photosynthetic rate (A) from leaf nitrogen content (N) is both conceptually and numerically important in models of plan~ecosystem and biosphere responses to global change. The relationship between A and N has been studied extensively at ambient C02 but much less at elevated C@.This study was designed to (1) assess whether the A-N relationship was more similar for species within than between community and vegetation types, and (2)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(83 citation statements)
references
References 40 publications
3
79
0
1
Order By: Relevance
“…Field & Mooney (1986) found that this relationship is quite general across species; this conclusion has been recently reinforced with an expanded dataset by Peterson et al (1999). However, Evans (1989) analysed the relationship in detail and suggested that, despite a general overall relationship, there was evidence of inter-specific differences in photosynthetic nitrogen-use efficiency, arising from differences in nitrogen allocation within the leaf.…”
Section: Photosynthetic Acclimation To Elevated Co 2 1489mentioning
confidence: 97%
“…Field & Mooney (1986) found that this relationship is quite general across species; this conclusion has been recently reinforced with an expanded dataset by Peterson et al (1999). However, Evans (1989) analysed the relationship in detail and suggested that, despite a general overall relationship, there was evidence of inter-specific differences in photosynthetic nitrogen-use efficiency, arising from differences in nitrogen allocation within the leaf.…”
Section: Photosynthetic Acclimation To Elevated Co 2 1489mentioning
confidence: 97%
“…Nitrogen v www.esajournals.org enrichment significantly improved the growth efficiency, which was likely attributed to the increase of the leaf N content and the consequent promotion of photosynthetic capacity (Leuning et al 1995, Peterson et al 1999, Fleischer et al 2013.…”
Section: Minor N Limitation In the Old-growth Boreal Forestmentioning
confidence: 98%
“…Peterson et al 1999), m l the average CH 4 emission rate from attached leaves in the light, measured at 374 µg kg −1 DW h −1 by Keppler et al (2006), S l is specific leaf area, taken to be 20 m 2 kg −1 as an average for a range of species (Vile et al 2005) and 57 600 is a constant to convert from hours to seconds and mass-based to molar units for CH 4 emission. We then calculated CH 4 emission for each biome, m b , as:…”
Section: Photosynthesis-based Estimatesmentioning
confidence: 99%
“…This is estimated to consume between 10-44 Mt CH 4 year −1 globally (Ehhalt et al 2001), with oxidation rates strongly dependent on soil moisture conditions, being highest at intermediate soil moisture (e.g. MacDonald et al 1996;Price et al 2004). When soils are too wet, soil micro-sites become anaerobic and CH 4 is produced rather than oxidised.…”
Section: Methane Oxidation In Soilsmentioning
confidence: 99%